Risk of head and neck cancer in relation to blood inflammatory biomarkers in the Swedish AMORIS cohort - Yang, Yanping; Liang, Yushan; Sadeghi, Fatemeh; Feychting, Maria; Hamar, Niklas; Fang, Fang; Zhang, Zhe; Liu, Qianwei (Frontiers in Immunology, 2023)
Background: Inflammation is critically involved in the development of human cancer, and blood inflammatory biomarkers have been proposed to indicate the risk of different cancer types. Methods: Using the Swedish Apolipoprotein-Related Mortality Risk (AMORIS) Cohort (N=542,433), we first performed a time-to-event analysis to evaluate the association of the baseline level of 12 blood inflammatory biomarkers measured during 1985-1996 with the subsequent risk of head and neck cancer (HNC) identified through the nationwide Swedish Cancer Register until end of 2020. A nested case-control study was further conducted to demonstrate the longitudinal trends of the studied biomarkers during the 30-year period prior to diagnosis of HNC. Results: In the time-to-event analysis, we identified a total of 2,510 newly diagnosed HNC cases. There was an increased risk of HNC per standard deviation (SD) increase of haptoglobin (hazard ratio HR: 1.25; 95% confidence interval CI: 1.21-1.30), leukocytes (HR: 1.22; 95%CI: 1.17-1.28), sedimentation rate (HR: 1.17; 95%CI: 1.07-1.29), and monocytes (HR: 1.34; 95%CI: 1.07-1.68) at baseline, after adjustment for age, sex, fasting status, occupational status, and country of birth. In contrast, there was a decreased risk of HNC per SD increase of lymphocytes in % (HR: 0.85; 95%CI: 0.73-0.99) and lymphocyte-to-monocyte ratio (LMR) (HR: 0.81; 95%CI: 0.69-0.95) at baseline. In the nested case-control study using repeatedly measured biomarker levels, we found that individuals with HNC had consistently higher levels of haptoglobin, leukocytes, sedimentation rate, and monocytes, as well as consistently lower levels of lymphocytes in % and LMR, during the 30-year period prior to diagnosis, compared to controls. Conclusions: Based on a cohort of more than half a million participants with up to 35 years of follow-up, our findings provide solid evidence supporting the presence of alterations in blood inflammatory biomarkers during the decades before diagnosis of HNC.